Development of Cloud Detection Methods Using CFH, GTS1, and RS80 Radiosondes - 张金强 陈洪滨 卞建春 宣越健 段云俊 Maureen CRIBB (Advances in atmospheric sciences, 2012)
The accuracies of three instruments in measuring atmospheric column humidity were assessed during an upper troposphere and lower stratosphere observation campaign conducted from 7 to 13 August 2009 in Kunming, China. The three instruments are a cryogenic frost-point hygrometer （CFH）, a Vaisala RS80 radiosonde （RS80）, and a GTS1 radiosonde （GTS1）. The accuracy of relative humidity （RH） measurements made by the CFH, GTS1, and RS80 was similar between the surface and 500 hPa （～5.5 km above sea level）. However, above 500 hPa, the errors in RH measurements made by the RS80, relative to measurements made by the CFH, are much less than those detected with the GTS1. Three different retrieval methods for determining cloud boundaries from CFH, RS80, and GTS1 measurements were developed and take into account the differences in accuracy among the three instruments. The method for the CFH is based on RH thresholds at all levels, which demands high accuracy. Given that the accuracy of RH measurements decreases at higher altitudes, the cloud detection methods for RS80 and GTS1 are different for different altitude ranges. Below 5 km, the methods for the RS80 and the GTS1 are similar to that of the CFH; above 5 km, the methods for the RS80 and the GTS1 are both developed based on the second-order derivatives of temperature and RH with respect to height, but with different criteria applied. Comparisons of cloud-layer retrievals derived from the three measurements are also made.